Medicinal Plant Preparations in The Treatment of Diseases Oral Mucosa - Navro`zova Mavluda Muradovna (Scholars Digest Publishing, 2023)
The article presents a literature review about the use of drugs of medicinal plants in medical practice in diseases of the oral mucosa.
Keywords: herbal remedies; applications; combination with chemotherapy